ADAM SMITH AND ECONOMIC DEVELOPMENT IN THEORY AND PRACTICE: A REJECTION OF THE STADIAL MODEL?. Issue 1 (14th March 2022) - Paganelli, Maria Pia
Abstract : Adam Smith allegedly offers a model of economic development in both his Lectures on Jurisprudence and the Wealth of Nations —the so-called four stages of development model. The model presents a linear unfolding view of economic development from primitive to advanced stages. But Smith's own historical examples systematically contradict this model. I thus question whether Adam Smith actually endorses and uses the four stages model of development to illustrate development and suggest that if he does, he does it to discredit it instead. For Smith, history teaches that development is more accidental than fitting deterministic models.